Markers of Thrombin Generation Are Associated With Long-Term Clinical Outcome in Patients With ST-Segment Elevation Myocardial Infarction - Hansen, Charlotte Holst (Clin Appl Thromb Hemost, 2018)
Hypercoagulability in ST-segment elevation myocardial infarction (STEMI) as related to long-term clinical outcome is not clarified. We aimed to investigate whether prothrombin fragment 1+2 (F1+2), d-dimer, and endogenous thrombin potential (ETP) measured in the acute phase of STEMI were associated with outcome. Blood samples were drawn median 24 hours after symptom onset in 987 patients with STEMI. Median follow-up time was 4.6 years. Primary outcome was a composite of all-cause mortality, reinfarction, stroke, unscheduled revascularization, or rehospitalization for heart failure; secondary outcome was total mortality. The number of combined end points/total mortality was 195/79. Higher levels of d-dimer and F1+2 were observed with both end points (all P < .005), whereas ETP was significantly lower (P < .01). Dichotomized at medians, increased risk was observed for levels above median for F1+2 and d-dimer (combined end point P = .020 and P = .010 and total mortality P < .001, both), while an inverse pattern was observed for ETP (P < .02, both). Adjusting for covariates, d-dimer was still associated with reduced risk of total mortality (P = .034) and receiver operating characteristic curve analyses showed area under the curve of 0.700 (95% confidence interval, 0.640-0.758). The hypercoagulable state in acute STEMI seems to be of importance for clinical outcome.